2012
DOI: 10.1073/pnas.1118715109
|View full text |Cite
|
Sign up to set email alerts
|

Efficient genetic modification and germ-line transmission of primordial germ cells using piggyBac and Tol2 transposons

Abstract: The derivation of germ-line competent avian primordial germ cells establishes a cell-based model system for the investigation of germ cell differentiation and the production of genetically modified animals. Current methods to modify primordial germ cells using DNA or retroviral vectors are inefficient and prone to epigenetic silencing. Here, we validate the use of transposable elements for the genetic manipulation of primordial germ cells. We demonstrate that chicken primordial germ cells can be modified in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
127
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 60 publications
1
127
0
1
Order By: Relevance
“…At this time, chicken PGCs can be successfully maintained in vitro without the loss of germ cell integrity (32,33), and generating transgenic chickens is feasible using transposon elements in cultured chicken PGCs (18,34). This study demonstrated the creation of specific knockout chickens using TALENs.…”
Section: Discussionmentioning
confidence: 97%
“…At this time, chicken PGCs can be successfully maintained in vitro without the loss of germ cell integrity (32,33), and generating transgenic chickens is feasible using transposon elements in cultured chicken PGCs (18,34). This study demonstrated the creation of specific knockout chickens using TALENs.…”
Section: Discussionmentioning
confidence: 97%
“…Chicken PGCs are cultured and modified in vitro and then injected into embryos to generate transgenic chickens. Investigators have generated transgenic chickens and offspring efficiently using PB transposons (Macdonald et al, 2012;Park & Han, 2012). However, as is widely known, it is difficult to isolate many PGCs from embryos, and culturing PGCs in vitro is technically challenging and expensive.…”
Section: Discussmentioning
confidence: 99%
“…The SB transposon system was the first used to try and increase the transgene efficiency in chicken and turkey cells (Kong et al, 2008), while a germ-line-competent chicken PGC line was developed with the PB transposon and transposase, and both of the efficiency of transgenesis and the expression level of transgene were improved with these modified PGCs (Park & Han, 2012). A transgenic chick can be generated with the PGCs modified in vitro using both PB and Tol2 transposons (Macdonald et al, 2012). Lu et al (2015) first demonstrated that a PB transposon mediated the insertion of a transgene into chicken embryos during developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, transposon-mediated transgenesis was efficient for production of genetically modified livestock, namely swine [15][16][17] and chickens [18].…”
Section: Introductionmentioning
confidence: 99%